2020
DOI: 10.1590/0102-311x00196120
|View full text |Cite
|
Sign up to set email alerts
|

Comportamentos de proteção contra COVID-19 entre adultos e idosos brasileiros que vivem com multimorbidade: iniciativa ELSI-COVID-19

Abstract: Objetivou-se medir a ocorrência de comportamentos de proteção contra a COVID-19 e fatores sociodemográficos segundo a ocorrência de multimorbidade na população brasileira com 50 anos ou mais de idade. Foram utilizados dados de inquérito telefônico entre participantes do ELSI-Brasil (Estudo Longitudinal da Saúde dos Idosos Brasileiros), conduzido entre maio e junho de 2020. Avaliou-se o uso de medidas de prevenção não farmacológica para COVID-19, motivos para sair de casa segundo a presença de multimorbidade e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 40 publications
(50 reference statements)
0
7
0
8
Order By: Relevance
“…Most participants were older adults with comorbidities, the population group most susceptible to the more severe forms of the disease and to the economic, racial and gender inequalities that affect aging 25,26 . Even so, there were few reports of longitudinal follow-up by any SUS service during the pandemic or of support networks other than the family.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most participants were older adults with comorbidities, the population group most susceptible to the more severe forms of the disease and to the economic, racial and gender inequalities that affect aging 25,26 . Even so, there were few reports of longitudinal follow-up by any SUS service during the pandemic or of support networks other than the family.…”
Section: Discussionmentioning
confidence: 99%
“…Saúde Pública 2023; 39(2):e00163222 social distancing. In Brazil, studies show that individuals with comorbidities stayed more at home, with possible effects on the worsening of chronic problems 25 . The need to intensify local health surveillance, with a special focus on post-COVID patients and their immediate family, will more than ever require the family and community approaches of FHS, which were undermined by the new federal policy guidelines and funding 39 , which favor, for example, other models of PHC teams more focused on clinical and individual interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study, carried out in ten countries, found that there is an association between risk perception and the practices of preventive measures for COVID-19 (15) . Likewise, in Brazil, it has been reported that people who practice physical activity at the recommended levels are less likely to wear a mask when leaving home (21) and that the adoption of protective measures in people with multiple comorbidities was higher compared to people without comorbidity (22) . The finding that students under 20 years old are less likely to choose the N95 respirator compared to those over 30 could be explained by the invulnerability bias in which people, based on their personal characteristics, attribute who will have more favorable results compared to other people (23) .…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study, carried out in ten countries, found that there is an association between risk perception and the practices of preventive measures for COVID-19 ( 15 ) . Likewise, in Brazil, it has been reported that people who practice physical activity at the recommended levels are less likely to wear a mask when leaving home ( 21 ) and that the adoption of protective measures in people with multiple comorbidities was higher compared to people without comorbidity ( 22 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Otro estudio reciente realizado en diez países encontró que existe asociación entre la percepción de riesgo con las prácticas de medidas de prevención de la COVID-19 (15) . Asimismo, en Brasil, se ha reportado que las personas que practican actividades físicas en niveles recomendados tienen menor probabilidad de usar mascarilla al salir de su casa (21) y que la adopción de medidas de protección en personas con múltiples comorbilidades fue mayor en comparación con las personas sin comorbilidad (22) .…”
Section: Discussionunclassified